The Impact of Financial Reforms on FDI Inflow and Export Growth - Widjanarko, Yeremia Nicolaus (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: This study explores the interlinkages between financial reforms, FDI inflows, and export growth in China through the lens of the Neoclassical framework. It aims to understand how post-2000 banking deregulation and capital market liberalization contributed to expanding foreign investment and export performance—an issue highly relevant to policy evaluation in emerging economies. The research adopts a qualitative–empirical orientation grounded in established economic theory. Design/Methods/Approach: The analysis draws on secondary time-series data from 1992–2022 obtained from the World Bank and the Asian Development Bank, complemented by a thematic review of China's policy documents. The study examines the evolution of FDI, exports, and industrial value-added to assess the sequencing of reforms and their links to external performance. the qualitative-descriptive approach is deemed suitable for connecting institutional change with resource allocation dynamics and trade outcomes. Findings: The findings reveal that financial reforms—particularly banking deregulation and capital market opening—were associated with a thirty-fold rise in FDI inflows and a fifty-five-fold surge in exports. Thematic analysis also highlights that FDI-driven technology transfer enhanced manufacturing productivity, with industrial value-added increasing from roughly USD 625 billion (2004) to USD 4.98 trillion (2022). These results support the Neoclassical argument that reforms improving resource allocation efficiency are fundamental to sustaining export growth. Originality/Value: This research contributes by integrating macro-level quantitative evidence with an institutional qualitative perspective, offering a sequencing framework that emphasizes strengthening financial transparency before targeting FDI toward high-value-added sectors. Such an approach provides a transferable analytical lens for other developing economies. Practical/Policy implication: For policymakers, the study underscores the importance of prioritizing transparency and financial governance as prerequisites for attracting quality FDI. It also suggests designing selective incentives to channel investment into high-value-added industries that promote technology diffusion and export competitiveness. Details regarding institutional readiness indicators, policy instruments, and long-term evaluation mechanisms.